Pengalaman Bidan Dalam Memberikan Pelayanan Pada Pasien Riwayat Abortus Dan IUFD - wati, mega; syam, Azniah; sastika sumi, susi (STIKES Nani Hasanuddin, 2023)
Abstract Abortion and Iufd are perinatal deaths that have a traumatic impact not only for parents but also for health professionals who are directly involved, especially midwives who are one of the health workers who have an important role in preventing and treating these conditions. Regardless of the midwife's duties and role in this condition, describe her responses and coping mechanisms in the form of feelings of non-anxiety, anxiety, panic and sadness as well as adaptive and maladaptive coping mechanisms. The purpose of this study was to explore the experience of midwives in the form of response, coping and the midwife's point of view in providing services to patients with a history of abortion and Iufd. This study uses a type of qualitative research. The sampling procedure used was purposive sampling and the number of participants who participated in this study until data saturation occurred was 8 people. Data collection procedures by way of observation, interviews and documentation. Data analysis was carried out using the steps of data collection, data reduction, data presentation and drawing conclusions. Based on the results of the analysis, several themes were found, namely: (1) The involvement of village midwives in caring for patients with a history of miscarriage and stillbirth, (2) Causes of abortion and Iufd cases found by village midwives, (3) Actions taken by village midwives, (4) ) Response of village midwives caring for patients with abortion and Iufd, (5) Coping of village midwives treating patients with abortion and Iufd, (6) Support system that should support patients with a history of abortion and Iufd. And from the results of the analysis, not only involvement in handling but midwives also anxiety to the lack of previous experience in dealing with perinatal death. The recommendation in this study is to hold special training on maternal emergencies for midwives so they can be better prepared to deal with these conditions. Keyword: abortion, midwife, intrauterine fetal death, experience. Abstrak Abortus dan iufd adalah kematian perinatal yang berdampak traumatis tidak hanya bagi orang tua namun juga bagi professional kesehatan yang terlibat langsung, terkhusus bidan yang merupakan salah satu tenaga kesehatan yang memiliki peranan penting mencegah dan menangani kondisi tersebut. Terlepas tugas dan perannya bidan pada kondisi ini, mengambarkan respon dan mekanisme kopingnya berupa perasaan tidak cemas, kecemasan, kepanikan dan kesedihan serta mekanisme koping adaptif dan maladaptive. Tujuan penelitian ini yaitu untuk mengeksplorasi pengalaman bidan baik berupa respon, koping dan sudut pandang bidan dalam memberi pelayanan pada pasien riwayat abortus dan iufd. Penelitian ini menggunakan jenis penelitian kualitatif. Prosedur sampling yang digunakan adalah purposive sampling dan jumlah partisipan yang berpartisipasi dalam penelitian ini sampai dengan terjadi saturasi data sebanyak 8 orang. Prosedur pengumpulan data dengan cara observasi, wawancara dan dokumentasi. Analisis data dilakukan dengan menggunakan langkah-langkah pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Berdasarkan hasil analisis, ditemukan beberapa tema, yaitu: (1) Keterlibatan bidan desa dalam merawat pasien dengan riwayat keguguran dan kelahiran mati, (2) Penyebab kasus abortus dan iufd yang ditemukan bidan desa, (3) Tindakan yang dilakukan bidan desa, (4) Respon bidan desa merawat pasien dengan abortus dan iufd, (5) Koping bidan desa merawat pasien dengan abortus dan iufd, (6) Support sistem yang sebaiknya mendukung pasien dengan riwayat abortus dan iufd. Dan dari hasil analisis bukan hanya keterlibatan dalam penanganan tapi bidan juga merasakan duka disebabkan kurangnya pengalaman sebelumya dalam menanangani kematian perinatal. Rekomendasi dalam penelitian ini yaitu mengadakan pelatihan khusus tentang kegawatdaruratan maternal bagi bidan agar dapat lebih siap menghadapi kondisi tersebut. Kata kunci: Abortus; Bidan; Intrauterine Fetal Death; Pengalaman